2012
DOI: 10.2337/dc12-0515
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver, Insulin Resistance, and Features of Metabolic Syndrome

Abstract: OBJECTIVENonalcoholic fatty liver disease (NAFLD) coexists with insulin resistance (IR), but it is uncertain whether NAFLD and IR contribute independently to atherosclerosis. We tested whether fatty liver, IR, and metabolic syndrome (MetS) features (waist, glucose, triglyceride, HDL cholesterol [HDL-C], and blood pressure) were associated with a marker of atherosclerosis (coronary artery calcium [CAC] score >0), independently of cardiovascular risk factors and cardiovascular disease (CVD).RESEARCH DESIGN AND M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 32 publications
(27 reference statements)
5
79
1
4
Order By: Relevance
“…In another study using euglycemic hyperinsulinemic clamps, Fabbrini et al (37) found a significantly greater insulin resistance in liver, adipose, and muscle tissues from obese subjects with NAFLD compared with that observed in obese subjects without NAFLD, even though the two groups had been matched for VAT volume. With regard to the association between FL and CAC score O0, two recent studies involving large numbers of subjects showed that the association remained significant after controlling for traditional cardiovascular risk factors, including VAT (38) or pre-existing cardiovascular disease (39). Taken together, our results and those of other studies (36,37,38,39) strongly suggested that hepatic fat is intimately involved in the pathogenesis of metabolic abnormalities and subclinical atherosclerosis present in subjects with FL.…”
Section: European Journal Of Endocrinologysupporting
confidence: 75%
See 1 more Smart Citation
“…In another study using euglycemic hyperinsulinemic clamps, Fabbrini et al (37) found a significantly greater insulin resistance in liver, adipose, and muscle tissues from obese subjects with NAFLD compared with that observed in obese subjects without NAFLD, even though the two groups had been matched for VAT volume. With regard to the association between FL and CAC score O0, two recent studies involving large numbers of subjects showed that the association remained significant after controlling for traditional cardiovascular risk factors, including VAT (38) or pre-existing cardiovascular disease (39). Taken together, our results and those of other studies (36,37,38,39) strongly suggested that hepatic fat is intimately involved in the pathogenesis of metabolic abnormalities and subclinical atherosclerosis present in subjects with FL.…”
Section: European Journal Of Endocrinologysupporting
confidence: 75%
“…With regard to the association between FL and CAC score O0, two recent studies involving large numbers of subjects showed that the association remained significant after controlling for traditional cardiovascular risk factors, including VAT (38) or pre-existing cardiovascular disease (39). Taken together, our results and those of other studies (36,37,38,39) strongly suggested that hepatic fat is intimately involved in the pathogenesis of metabolic abnormalities and subclinical atherosclerosis present in subjects with FL. The adverse cardiovascular risk profile found in subjects with SCH plus FL may serve as a marker of long-term cardiovascular risk and may explain some of the previously observed associations between SCH and cardiovascular disease (10,33).…”
Section: European Journal Of Endocrinologysupporting
confidence: 75%
“…[15][16][17] The present study showed that the prevalence of NAFLD was highest in more than 40 years age group & in males. The findings of the study is in line with the Kalra et al study where the prevalence was the highest in 60-70 year age group.…”
Section: Discussionmentioning
confidence: 73%
“…Even in the absence of DM, higher blood glucose levels, higher hemoglobin A1c levels, and insulin resistance (IR) have been shown to be associated with an increased risk of ASCVDs (87)(88)(89). IR plays crucial roles in atherosclerosis (90), and it has been clarified that IR was positively associated with coronary severity (91), the coronary calcium score (92), and a remodeling index (93). Various past studies in basic research have supported the results of these clinical trials.…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 97%